2015
DOI: 10.4236/ampc.2015.55019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effect of Temperature on the Corrosion Behaviour of 2205 Duplex Stainless Steel and 316 Austenitic Stainless Steel in Acidic Chloride Environment

Abstract: The 2205 duplex stainless steel and 316 austenitic stainless steels were studied in 1 M sulphuric acid and 1% NaCl solution. The microstructures of the specimens were investigated with scanning electron microscopy with energy dispersive X-ray analysis. X-ray Diffraction analysis was used for phase analysis. The electrochemical behaviour was evaluated using potentiodynamic method. The results show that the critical current density is higher for 316 austenitic stainless steels than 2205. The passive range was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…One study showed that R 1 indicates the stability of the passive film and R ct denotes the charge transfer resistance, which means larger R 1 and R ct indicate better coating corrosion resistance [40]. CPE is used to replace the capacitor in the circuit to compensate the influence of the surface uniformity of the coatings [41]. The impedance of the CPE is expressed by the formula below:…”
Section: Eis Analysismentioning
confidence: 99%
“…One study showed that R 1 indicates the stability of the passive film and R ct denotes the charge transfer resistance, which means larger R 1 and R ct indicate better coating corrosion resistance [40]. CPE is used to replace the capacitor in the circuit to compensate the influence of the surface uniformity of the coatings [41]. The impedance of the CPE is expressed by the formula below:…”
Section: Eis Analysismentioning
confidence: 99%